1953
DOI: 10.3402/tellusa.v5i3.8594
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Electron Orbits in the Field of a Magnetic Dipole: Part II

Abstract: In the preceding issue of Tellus were pub- lished the first results of our investigations of cosmic ray orbits in the field of a magnetic dipole. The investigations were carried out by measurements o n a model with particle mo- mentum range corresponding to 1010-eV/c. A detailed description of the apparatus and the performance of the experiment is given in part I of the present paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1958
1958
1965
1965

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using the data on the trajectories obtained in this way, Brunberg and Dattner [4] have shown that it is possible to account for the daily variation observed with counter telescopes pointing in the north and south directions at 30 0 to the vertical if it is assumed that the mean energy of the primary radiation responsible for the variation lies in the region 2 to 4 x io 10 eV. With this assumption, an anisotropy of the primary radiation with a direction lying near the plane of the ecliptic would produce a daily variation of nearly the same amplitude for the north and south directions but with a phase difference of about 2 hr as was indeed observed in 1948 and 1949 (Malmfors[2] 3 Elliot and Dolbear [i]). …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Using the data on the trajectories obtained in this way, Brunberg and Dattner [4] have shown that it is possible to account for the daily variation observed with counter telescopes pointing in the north and south directions at 30 0 to the vertical if it is assumed that the mean energy of the primary radiation responsible for the variation lies in the region 2 to 4 x io 10 eV. With this assumption, an anisotropy of the primary radiation with a direction lying near the plane of the ecliptic would produce a daily variation of nearly the same amplitude for the north and south directions but with a phase difference of about 2 hr as was indeed observed in 1948 and 1949 (Malmfors[2] 3 Elliot and Dolbear [i]). …”
Section: Introductionmentioning
confidence: 84%
“…The trajectories of cosmic ray particles in the earth's field have been investi gated by Brunberg and Dattner [3] by means of scale model experiments. Using the data on the trajectories obtained in this way, Brunberg and Dattner [4] have shown that it is possible to account for the daily variation observed with counter telescopes pointing in the north and south directions at 30 0 to the vertical if it is assumed that the mean energy of the primary radiation responsible for the variation lies in the region 2 to 4 x io 10 eV.…”
Section: Introductionmentioning
confidence: 99%
“…The primaries of rigidity R that are responsible for J (R, wr) will have approached the Earth's magnetic field from directions within some asymptotic volume element (Qr)R specified by latitude (Dr)R and longitude (<Pr)R. Such asymptotic coordinates are usually found either by computing the trajectories of the primaries outward from the direction (Zr, arJ at the geomagnetic location of the recorder (see McCracken, Rao, and Shea 1962), or else from observations of thc deflections of charged particles in a physical simulation of the geomagnetic field (see the terrella experiments of Brunberg and Dattner 1953). When J(R, wr) and the associated asymptotic coordinates (8 r )R and (</>r)R have been calculated for each of the volume elements Wr that make up the solid angle of the recorder, the distribution of the fractional f-L-meson intensity due to primaries of rigidity R can be determined with respect to both asymptotic latitude and asymptotic longitude of the primaries.…”
Section: Methods Of Determining Vial As a Function Of Rumentioning
confidence: 99%
“…Consequently, the particle deflections were estimated from the diagrams of Brunberg and Dattner (1953) for the geomagnetic southern latitude of 50°. Considerable interpolation was necessary and for this reason it was found more convenient to express the asymptotic latitude and longitude data in the form of deflections in zenith angle and azimuth.…”
Section: Application To the Cosmic Ray Detectors (A) The Verticalmentioning
confidence: 99%